2018
DOI: 10.2341/16-206-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Stress on Simulated Localized and Generalized Wear of Nanofilled Resin Composites

Abstract: The simulated localized and generalized wear of nanofilled resin composites is material dependent. The simulated localized wear of nanofilled resin composites appears to be influenced by thermal stress, whereas this effect is not as apparent in simulated generalized wear testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…After placement of the repair composite, additional thermal cycling was performed to assess the long-term stability. As opposed to water storage (aging due to water uptake only), thermocycling simulates hydrothermal aging with temperature changes resulting in repetitive contraction-expansion stresses (24,28). The number of cycles used (10,000 cycles) might correspond to approximately one year of clinical service (29).…”
Section: Discussionmentioning
confidence: 99%
“…After placement of the repair composite, additional thermal cycling was performed to assess the long-term stability. As opposed to water storage (aging due to water uptake only), thermocycling simulates hydrothermal aging with temperature changes resulting in repetitive contraction-expansion stresses (24,28). The number of cycles used (10,000 cycles) might correspond to approximately one year of clinical service (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to conventional types of DRCs, the quantity, type, size of the inorganic filler [7], and the silanization of the inorganic filler significantly influence the mechanical properties [8]. The mechanical properties of FRCs depend on two main variables: the type of organic matrix [9,10], which gives the mechanical properties of the organic part [11,12], and the inorganic filler [13], characterized by the type, size, and geometry [13,14]. Other factors that influence the mechanical behavior of FRCs are the silanization [8], factors affecting the polymerization efficiency [15,16], and the binding between the inorganic filler and the organic matrix [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, there was a clear relationship between wear resistance and average filler size of indirect composite resins. The complexity of wear resistance is further pointed out by another study22 in which newly developed conventional composite resins showed variations with same wear simulation that could not be explained purely in terms of filler particle size.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the wear characteristics of NX and GP appear to be close to those of Filtek P50. Tsujimoto et al22 also reported that the clinical wear rate of Filtek P50 was measured as 8.3 µm/year in 2004 and 2008 at the CU and 7.8 µm/year in 2004 at the Catholic University of Leuven School of Dentistry (CL). Therefore, combining the results of this study and previous studies, clinicians can predict the likely clinical wear rates of GP and SN (approximately < 10 µm/year) and understand that other indirect composite resins may have higher wear rates (> 10 µm/year).…”
Section: Discussionmentioning
confidence: 99%